IDENTIFICATION, SYNTHESIS AND CHARACTERIZATION OF RELATED SUBSTANCES OF PRASUGREL - P. Pratap Reddy, A. Sampath,V. Prabhakar Reddy*, G. Goverdhan, G. Nagaraju (Journal of Pharmaceutical Research and Opinion, 2014)
During the process development of Prasugrel, six related substances (impurities) ranging from 0.05 to 0.15 % were detected by a gradient high performance liquid chromatography (HPLC) method. Liquid chromatography–mass spectrometry (LC–MS) was performed to identify the molecular mass of these impurities. A detailed study was undertaken to characterize all the impurities. These impurities were synthesized and co-injected with sample containing the impurities and found the retention time match of the spiked impurities. Based on the spectral data (IR, NMR and MS), these impurities were characterized as 5-[2-cyclopropyl-1-(2-fluorophenyl)-2-oxoethyl]-5,6,7,7a-tetrahydrothieno[3,2-c]pyridin-2(4H)-one impurity-I, this impurity was eluted as two peaks at retention time 22.1 and 23.2 minutes in the HPLC analysis due to the keto-enol tautomerism), 5-[2-cyclopropyl-1-(3-fluorophenyl)-2-oxoethyl]-4,5,6,7-tetrahydro thieno[3,2-c]pyridin-2-yl acetate (impurity-II), 5-[2-cyclopropyl-1-(4-fluorophenyl)-2-oxoethyl]-4,5,6,7-tetrahydrothieno[3,2-c]pyridin-2-yl acetate (impurity-III), 5-(2-cyclopropyl-2-oxo-1-phenylethyl)-4,5,6,7-tetrahydrothieno[3,2-c]pyridin-2-yl acetate (impurity-IV), 5-[1-(2-fluoro phenyl)-2-oxopropyl]-4,5,6,7-tetrahydrothieno[3,2-c]pyridin-2-yl acetate (impurity-V) and 5-[2-cyclopropyl-1-(2-fluorophenyl)-2-oxoethyl]-4,5,6,7-tetrahydrothieno[3,2-c]pyridin-2-yl propionate (impurity-VI). Impurities II, III, IV and VI are hitherto not reported in the literature.